IMAM SUYUTI’S ORIGINAL THOUGHT ON THE OPPOSITION TO (GREEK) LOGIC AND THEOLOGY IN SAWN AL-MANTIQ WA‘L-KALAM ‘AN FANNAY AL-MANTIQ WA‘L-KALAM* - MUFTI ALI (Hamdard Islamicus, 2021)
The transmission of Greek philosophy and sciences to the Islamic world through the translation movement in the eighth and ninth centuries played a major role in accelerating the Hellenizing process of that world. The emergence of scholastic theology (kalÉm) and Islamic Aristotelianism and Neo-Platonism (falsafah) in the Islamic world is considered, in Madjid’s opinions, as the direct cultural influence of it.